Renewable Energy Regulations in Indonesia and India: A Comparative Study on Legal Framework - Karim, Ridoan; Ghazali, Farahdilah; Ansari, Abdul Haseeb (Universitas Negeri Semarang, 2020)
Individually and collectively, climate change has become the international agenda due to global warming and unusual weather patterns. The International Renewable Energy Agency (IRENA) claims that the future world can only survive if the human civilisation takes a drastic turn towards renewable;e energy production. Besides, the pandemic COVID-19 has ventured us to revisit our behaviour towards the environment. Indonesia and India, being two giant economies, has promised under the Paris Climate Agreement to support the international agendas of climate change and sustainable development goals. Many countries have shown their commitment to lower their carbon emissions by using renewable energy sources significantly. Renewable energy generation opens a feasible door to attempts to combat climate change. This comparative analysis assesses the renewable energy laws and policies in Indonesia and India, as they work towards their climate change commitments (UNFCCC). This research operates within comparative qualitative methodological structures and uses secondary empirical sources. Building on similar and relative exposures, both the countries should benefit from each other and learn the legal and political implications to speed up the production of renewable energy and reduce greenhouse gas (GHG) emissions.